(untitled) (Nepalese Journal of Radiology, 2022)
Introduction: Determination of fetal weight is important for the management during labour and delivery. It helps in determining the mode of delivery and aids in diagnosing low birth weight, macrosomia, and intrauterine growth restriction fetus. Ultrasound may not be available in under-resourced settings. Therefore, it is important to study the accuracy of clinical estimation of fetal weight with the sonographic and actual birth weight. Methods: One hundred and fifty women fulfilling the inclusion criteria were enrolled for the study. Clinical estimation of fetal weight was done by using the Johnson formula. Then the women were subjected to ultrasound. Sonographic estimation of fetal weight was done by the Hadlock method. The two estimated fetal weights were then compared with the actual birth weight. Data were analyzed using SPSS (VERSION 16). Results: Actual birth weight has a strong correlation with the ultrasonographic birth weight (p=0.01). However, the clinical birth weight estimation was less correlating to the actual birth weight (p=0.638) Conclusion: The ultrasound method is better in determining the actual birth weight as compared to the clinical method. Hence, ultrasound has to be recommended whenever available.